METHODOLOGICAL AND APPLIED ASPECTS OF RESOURCE MANAGEMENT IN THE SYSTEM OF ECONOMIC SECURITY OF INDUSTRIAL ENTERPRISES - VASYLTSIV, Taras; LUPAK, Ruslan; MYKYTYN, Oleh (Herald of Khmelnytskyi National University. Economic sciences, 2025)
In the system of the economic potential of the enterprise (along with competitive, innovative, production, marketing and sales, organizational and managerial and entrepreneurial potentials), in particular in the field of industry, a significant role is assigned to the management of resource provision - a functional and structural element of the economic security of the enterprise, which determines the quality of processes formation and effective use of resources in order to maintain the stability and sustainability of the economic security of the enterprise. The components of resource provision of industrial enterprises should be considered: production, resource-raw material, technical-technological, intellectual-personnel, financial-investment, intangible, scientific-technical, infrastructural, marketing, logistic, information and environmental. The decisive role of the management of resource provision of industrial enterprises in the system of guaranteeing their economic security is confirmed by the performance of such tasks as the formation of resource provision of the production process for the implementation of the production program and the plan of strategic development of production; innovative and technological modernization of the production complex, strengthening of the technological competitiveness of products and enterprises; effective use of intellectual and personnel and scientific and technical support; development of the resource support system for development and market introduction of new samples of competitive products; digitization of business processes and the growing role of IT support for production activities and marketing and communication processes; accumulation of the resource base of access to foreign markets, integration into global distribution networks of industrial products.
Keywords: resource provision; economic security; industrial enterprises; management; activity; potential; resources; production; technologies